Autonomous adaptation to climate change by shrimp and catfish farmers in Vietnam's Mekong River Delta - Kam, Suan Pheng; Badjeck, M.C.; Teh L; Tran N (2012)
The Mekong River delta of Vietnam supports a thriving aquaculture industry but is exposed to the impacts of climate change. In particular, sea level rise and attendant increased flooding (both coastal and riverine) and coastal salinity intrusion threaten the long-term viability of this important industry. This working paper summarizes an analysis of the economics of aquaculture adaptation in the delta, focusing on the grow-out of two exported aquaculture species the freshwater striped catfish and the brackish-water tiger shrimp. The analysis was conducted for four pond-based production systems: catfish in the inland and coastal provinces and improved extensive and semi-intensive/intensive shrimp culture.